1998
DOI: 10.1161/01.hyp.32.2.187
|View full text |Cite
|
Sign up to set email alerts
|

Renal Dopamine Receptor Function in Hypertension

Abstract: Abstract-Dopamine plays an important role in the regulation of renal sodium excretion. The synthesis of dopamine and the presence of dopamine receptor subtypes (D 1A , D 1B as D 1 -like and D 2 , and D 3 as D 2 -like) have been shown within the kidney. The activation of D 1 -like receptors located on the proximal tubules causes inhibition of tubular sodium reabsorption by inhibiting Na,H-exchanger and Na,K-ATPase activity. The D 1 -like receptors are linked to the multiple cellular signaling systems (namely, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
245
1
10

Year Published

2000
2000
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(264 citation statements)
references
References 111 publications
(161 reference statements)
8
245
1
10
Order By: Relevance
“…13 These effects have been thoroughly analysed and characterised by two kinds of response, depending on whether it is produced by D 1 or D 2 . Activation with selective agonists to D 1 receptors results in hypotension, increase in renal flow, 14 diuresis, and natriuresis, whereas stimulation of D 2 produces hypotension, bradycardia, decrease in afterload and vasodilatation in certain vascular beds 15 (see Table 1). These effects are Na + dependant, ie, increases in plasma [Na + ] induce higher excretion of water and Na + , and result in high dopamine levels in urine.…”
Section: Role Of Dopamine In Kidney Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 These effects have been thoroughly analysed and characterised by two kinds of response, depending on whether it is produced by D 1 or D 2 . Activation with selective agonists to D 1 receptors results in hypotension, increase in renal flow, 14 diuresis, and natriuresis, whereas stimulation of D 2 produces hypotension, bradycardia, decrease in afterload and vasodilatation in certain vascular beds 15 (see Table 1). These effects are Na + dependant, ie, increases in plasma [Na + ] induce higher excretion of water and Na + , and result in high dopamine levels in urine.…”
Section: Role Of Dopamine In Kidney Functionmentioning
confidence: 99%
“…DA reversibly inhibits this pump, mainly through type 1 receptors, which results in an increase in natriuresis. 4,15 The second messengers responsible for the enzyme phosphorylation are apparently phospholipase A 2 (PLA 2 ), with the subsequent release of arachidonic acid and its metabolites, and phospholipase C (PLC). Their actual distribution and mediation seem to be of dependent nature.…”
Section: Role Of Dopamine In Kidney Functionmentioning
confidence: 99%
“…In vivo, increases in dietary sodium intake or acute sodium loading lead to natriuresis accompanied by elevated urinary dopamine excretion, which suggested that dopamine produced endogenously by the epithelial proximal tubule cells might contribute to the natriuretic response (2)(3)(4). In this model, endogenously produced dopamine would be transported outside the proximal tubule cells where it binds to specific cell membrane receptors.…”
mentioning
confidence: 96%
“…In recent years, an increasing number of publications (1)(2)(3)(4) have reported the short term regulation of kidney Na ϩ ,K ϩ -ATPase by hormones and intracellular second messengers that modulate proximal tubule sodium reabsorption. Renal Na ϩ ,K ϩ -ATPase activity is regulated by phosphorylation/dephosphorylation processes, and both cAMP-dependent protein kinase and protein kinase C (PKC) phosphorylate the Na ϩ ,K ϩ -ATPase (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). We have demonstrated that Ser-18 of the ␣-subunit is essential for the inhibition of the Na ϩ -pump activity by dopamine and that both Ser-18 and Ser-11 are essential for the stimulation of this activity by PMA (10 -15).…”
mentioning
confidence: 99%
See 1 more Smart Citation